Keurig : from David to Goliath : the challenge of gaining and maintaining marketplace leadership - Anderson, Eric T. (SAGE knowledge. Cases., 2016)
From 2002 to 2011, coffee-machine manufacturer Keurig had grown from a privately held company with just over $20 million in revenues to become a wholly owned subsidiary of Green Mountain Coffee Roasters, a publicly traded company with net revenues of $1.36 billion. This case examines the rapid rise of Keurig.